Vernakalant and electrical cardioversion for AF – Safe and effective. (September 2019) - Simon, Alexander; Niederdoeckl, Jan; Janata, Karin; Spiel, Alexander Oskar; Schuetz, Nikola; Schnaubelt, Sebastian; Herkner, Harald; Cacioppo, Filippo; Laggner, Anton Norbert; Domanovits, Hans
Abstract: Aims: Rapid restoration of sinus rhythm is an integral part of the management of recent-onset atrial fibrillation. We aimed to assess safety and efficacy of vernakalant, a multi-channel blocking agent, in combination with external electrical cardioversion. Methods: This prospective cohort study comprised 230 patients (female 35%; median age 50 IQR 42–55) with recent-onset AF presenting to a university tertiary care center during a 6-year period. Management included intravenous vernakalant followed by electrical cardioversion in case of pharmacological failure. Results: Within 11 min (IQR 8–29), sinus rhythm could be restored by sole pharmacological management in 167 patients (73%). A left ventricular function lower than 55% (OR 3.51 (1.45–8.52)) and prior atrial fibrillation episodes being classified as persistent (OR 2.33 (1.13–4.80)) were significant predictors for non-response to vernakalant. Electrical cardioversion was successful in all patients but one within 196 min (IQR 149–300) of administration of first dosage of vernakalant. No serious adverse events could be observed. 3 patients needed further in-patient care. Conclusion: Management of recent-onset atrial fibrillation consisting of intravenous vernakalant followed by electrical cardioversion in case of failure appears safe and efficacious. Achieving a rapid conversion, this approach could potentially save resources and costs.